1997
DOI: 10.1523/jneurosci.17-11-04056.1997
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Diurnal Rhythms of Serotonin 5-HT2Cand Corticosteroid Receptor Gene Expression in the Hippocampus with Food Restriction and Glucocorticoids

Abstract: Both serotonergic dysfunction and glucocorticoid hypersecretion are implicated in affective and eating disorders. The adverse effects of serotonergic (5-HT) 2C receptor activation on mood and food intake, the antidepressant efficacy of 5-HT 2 receptor antagonists, and the hyperphagia observed in 5-HT 2C receptor knockout mice all suggest a key role for increased 5-HT 2C receptor-mediated neurotransmission. Glucocorticoids, however, downregulate 5-HT 2C receptor mRNA in the hippocampus, and it is unclear how i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 51 publications
1
54
1
Order By: Relevance
“…The expression of glucocorticoidand mineralcorticoid receptor mRNA (Holmes et al, 1995), as well as 5-HT2C receptor mRNA expression (Holmes, French, & Seckl, 1997), shows diurnal rhythms. The hippocampus also expresses rhythmicity in Jun-B and c-fos mRNA (Menegazzi et al, 1994) and in Fos protein levels (Kononen et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of glucocorticoidand mineralcorticoid receptor mRNA (Holmes et al, 1995), as well as 5-HT2C receptor mRNA expression (Holmes, French, & Seckl, 1997), shows diurnal rhythms. The hippocampus also expresses rhythmicity in Jun-B and c-fos mRNA (Menegazzi et al, 1994) and in Fos protein levels (Kononen et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…However, others have found that POMC is reduced after a period of CR (9,49). Although circulating corticosterone (CORT) levels are often increased after CR (27,33,47,64), earlier components of the hypothalmic-pituitary-adrenal axis (HPA) axis are often unaffected, such as ACTH, which is synthesized from POMC (1). This highlights that HPA axis alterations after CR have yet to be fully understood.…”
Section: Cr Sickness Behavior and A Potential Mechanismmentioning
confidence: 99%
“…One possible mechanism by which CR exerts its antiinflammatory effect are glucocorticoids, which are increased after CR (33,47) and act to increase the transcription of anti-inflammatory cytokines and decrease the transcription of proinflammatory cytokines (4). Indeed, CR reduces both basal and LPS-stimulated levels of TNF-␣ and IL-6 mRNA in alveolar macrophages in rats (18).…”
mentioning
confidence: 99%
“…Expression of the 5-HT transporter fluctuates over time and affects citalopram binding, sleep behaviors, brain 5-HT levels, 5-HT 1A receptors, and 5-HIAA levels (Fabre et al 2000). Both citalopram binding at the serotonin transporter (Kulikov et al, 1997) and 5-HT 2C receptor RNA expression (Holmes et al, 1997) increase significantly during morning hours. Monoamine function varies diurnally in rodent hypothalamus slices (Blier et al, 1989) and 5-HIAA rhythms vary regionally in rodent microdialysis studies (Nakayama, 2002).…”
Section: Introductionmentioning
confidence: 99%